Choice-making at Tier 2: Linking and adapting choice by type and function. Issue 1 (2nd January 2020) - Jolivette, Kristine; Ennis, Robin Parks; Swoszowski, Nicole Cain
Abstract: Choice-making is a strategy that can be implemented across varying age levels and abilities to target problem behavior as well as academic engagement/performance. It can be embedded within multitiered systems of support frameworks as an individual or group approach as well as a Tier 1 or 2 strategy, depending on students' need and response, thus requiring limited planning and resources on the part of educators. This article presents the systematic steps for implementing choice-making as well as a variety of choice options along with the process for adapting choice at Tier 1 and Tier 2. In addition, function-based choice-making is described and classroom-based illustrations of function-based choice provided.